Metformin anticancer: Reverses tumor hypoxia induced by bevacizumab and reduces the expression of cancer stem cell markers CD44/CD117 in human ovarian cancer SKOV3 cells - Fan, Yuanchun; Cheng, Huimin; Liu, Yueping; Liu, Shihao; Lowe, Scott; Li, Yaru; Bentley, Rachel; King, Bethany; Tuason, John Pocholo W.; Zhou, Qin; Sun, Chenyu; Zhang, Hui (Frontiers in Pharmacology, 2022)
Blocking angiogenesis is a new therapeutic strategy to inhibit tumor growth. The anti-angiogenic drug bevacizumab has been approved for gynecological malignancies, especially for advanced recurring cervical cancers and recurring ovarian cancers (OC). Studies have shown that bevacizumab may aggravate TME hypoxia, help maintain the stemativity of ovarian cancer stem cells (CSCs), and promote cancer cell invasion and metastasis. Drugs that target CSCs, such as metformin, may enhance the efficacy of antivascular therapy. Therefore, we made a bold guess that anti-angiogenesis drugs combined with anti-Cscs drugs could improve the anti-tumor effect.In vitro test results in this study showed that combination therapy of Metformin and bevacizumab significantly reduced the proliferation rate of SKOV3 cells and the growth rate of transplanted tumors in nude mice compared with the monotherapy effects. In vivo results showed that metformin significantly reduced the proportion of CD44+/CD117+ CSCs. Although bevacizumab increased the proportion of CD44+/CD117+ CSCs, the addition of metformin did offset this fluctuating trend. The combination of bevacizumab, metformin, and cisplatin efficiently decreased the proportion of CSCs in the OC animal model. IHC results exhibited that expressions of VEGF, CD34, and HIF-1α in transplanted tumors were decreased by metformin alone compared with the control (P<0.05). In the bevacizumab treatment, VEGF, and CD34 expressions were decreased, while that of HIF-1α was increased, suggesting that the degree of hypoxia was differentially aggravated after the bevacizumab treatment. The VEGF, CD34, and HIF-1α expressions in the bevacizumab + metformin + cisplatin group were the lowest among all other treatment groups (P<0.05). Subcutaneous statistics of nude mice reseeded by the limit dilution method showed that the tumor recurrence rate in the bevacizumab + metformin + cisplatin group was relatively lower.In this study, bevacizumab treatment aggravated the degree of hypoxia in the TME, induced overexpression of HIF-1α, and increased the proportion of CD44+/CD117+ CSCs. While metformin could alleviate the hypoxic condition in the TME inhibiting the growth of CSCs. The combination of metformin, bevacizumab, and platinum-based chemotherapeutic cisplatin may be a reasonable and promising treatment option to improve the prognosis of OC patients